Effectiveness of Teriparatide on Fracture Healing: A Systematic Review and Meta-Analysis. - Zhongju Shi; Hengxing Zhou; Bin Pan; Lu Lu; Jun Liu; Yi Kang; Xue Yao; Shiqing Feng (PLoS ONE)
Purpose Nowadays, the efficacy of teriparatide in treating osteoporosis was widely accepted, but the discussion about using teriparatide to enhance fracture healing hasn't come to an agreement. This meta-analysis was conducted to evaluate the effectiveness of teriparatide for fracture healing. Methods We searched PubMed, the Cochrane Library, and Embase in August 2016 for randomized controlled trials (RCTs) which concerned the treatment of teriparatide for fracture healing. Results Finally, a total of 380 patients were randomly assigned in the 5 trials included in this meta-analysis. There was a significant effectiveness with regards to function improvement in patients following fracture, however, there was no significant effectiveness with regards to time of radiographic fracture healing, fracture healing rate and reduction in pain. Conclusions This analysis showed that administration of teriparatide following fracture lacked the effectiveness for fracture healing. Moreover, teriparatide administration had no apparent adverse effects. These results should be interpreted with caution because of some clear limitations. If we want to confirm whether teriparatide improves fracture healing, more high-quality randomized controlled trials are needed.